Rectal swabs vs bulk faeces PCR testing for the diagnosis of enteric conditions (RecSwabFaeces): Protocol for a single group diagnostic accuracy comparative trial - Madisen Sadie Roser; Megan K. Young; Dustylee Williams; Shradha Subedi; Donna Barnekow; Alyssa Pyke; Jacob Tickner; Glen Hewitson; Michael Thomas; Gulam Khandaker; Sanmarie Schlebusch; Nicolas Roydon Smoll (PLoS ONE, 2025)
Obtaining a stool specimen for diagnostic testing of enteric conditions (e.g., gastroenteritis) can be a challenging and unpleasant experience. A person is required to obtain a sample pot from a healthcare location, return home and wait until they have a bowel motion, and then deal with the challenges of returning the sample to the clinic or pathology centre. This trial aims to identify whether the simpler approach of obtaining a rectal swab is effective for diagnosing enteric conditions. Recruitment will take place in a variety of settings, including suspected norovirus clusters, Hepatitis A clusters, in both hospital, and community settings. We will compare paired stool and rectal swab sample polymerase chain reaction (PCR) testing to determine whether rectal swabs are a reliable proxy for faecal sampling. Persons who would normally be provided with a faecal specimen container, will also be provided with a rectal swab for self-collection or clinician-collection (within 24 hours of the bulk faeces collection). We will assess the sensitivity, specificity, positive predictive value, negative predictive value using standard confusion matrix. The gold standard reference will be considered the bulk faeces PCR tests. We hypothesise that rectal swab PCR testing will be equally as effective as bulk faeces PCR testing. If successful, rectal swab PCR testing could be implemented as routine practice with several key benefits. Firstly, it would improve the patient experience by conveniently enabling stool collection at the point of care, which is rarely possible currently. Secondly, it would reduce healthcare costs, and streamline collection processes by eliminating the need for persons to return to a clinic to deliver specimen. Thirdly, the ease of testing will likely increase testing rates and compliance, leading to better diagnoses and more accurate clinical care. The protocol described has the potential to revolutionise daily clinical practice. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12624000095561.